Influencia del método GRAMMAR TRANSLATION en el aprendizaje cognitivo del idioma ingles en estudiantes del 3º "C" nivel secundaria, de la I.E. "Tarapoto", en el año 2010 - Garcia Pinchi, Luis Enrique (2010)
This research focuses on the study of the influence of the GRAMMAR TRANSLATION method in the cognitive English learning. lt realized a review of the relevant literature for points to research they were cognitive information processing, learning, cognitive learning, method, GRAMMAR TRANSLA TION method, technique, and the research "Método Didáctico CLAFEL IV y sus influencias en el aprendizaje del idioma inglés en educandos del tercer grado de educación secundaria." Each of the themes was detailed, to obtain a clear understanding of the points and to achieve the goals set. We applied a PRE TEST and a POST TEST of 20 questions each one, with the purpose to measure the influence of the GRAMMAR TRANSLATION method in the cognitive English learning, it was taken into account three dimensions of cognitive learning: memory, analysis and synthesis; it developed six learning sessions, it applied an evaluation for researchers to know if students are satisfied with the work performed, the evaluation had three components: methodology, materials, evaluation. Thanks to the analysis of the results, we can observe that the GRAMMAR TRANSLATION method influence in the cognitive English learning, we made tables and charts where we can observe with the naked eye the results of the evaluation and learning sessions and which allowed to realize the conclusions that support or refute the hypothesis established. This research present as studio it can provide a guideline to realize another researches related with the theme, suggest sorne points which can improve the teaching of English.